Noise trading and the valuation of initial public offerings in Singapore. - Tan, Meng Kim. (2010)
Past studies done on the initial public offering (IPO) market have largely found that IPOs experience high positive first-day but insignificant negative long-term aftermarket abnormal returns. Researchers have widely accepted this as an underpricing phenomenon by issuers and underwriters to attract the interest of investors. Evidence of any pricing inefficiency in the IPOs' long-run aftermarket are hotly debated. This research differs from past long-term studies by concentrating on the shortterm aftermarket performance of IPOs. A significant negative relationship is established between the initial and short-term aftermarket abnormal returns of IPOs. This contrasts with previous studies and provides evidence of a short-term pricing inefficiency in the IPO market. It suggests the presence of a transitory component in the initial IPO price.